Young male fishers of Baybay Norte, Miag-ao, Iloilo their socio-demographic profile, perception and attitude towards fishing - Dela Cruz, Beulah Campoy
This is a descriptive study aimed to determine the following objectives: (1) the socio-demographic profiles of the young male fishers, (2) their perceptions and (3) their attitudes towards fishing. , Questionnaires were utilized to determine the socio-demographic profile and perception of the participants. On the attitude of the participants, Likert scale was used. It was found out that majority of the participants are single who reached high scholl level of education, and started fishing at the age of 13-16. Most of them value fishing because they viewed that there are no other jobs to venture in. A greater number of the participants have neither positive nor negative towards fishing.